The Influence of Leadership Style, Organizational Culture and Discipline on Employee Performance - Windayati, Diana Titik; Sinta, Dwi (Zona Manajerial: Program Studi Manajemen (S1), 2022)
This study aims to obtain empirical evidence about the influence of leadership style, organizational culture and discipline on employee performance. This research was conducted at the Batam City Regional Tax and Retribution Management Agency. The population in this study were all employees at the Batam City Regional Tax and Levies Management Agency. Then a sample of 143 respondents was taken using the slovin method. The test method used is multiple regression. The results of this study indicate the effect of leadership style, organizational culture and discipline simultaneously using the F test, obtained the calculated F value of 60,540 with a significance level (sig) = 0.000. because the value of 0.000 <0.05, thus Ho is rejected and Ha is accepted, the regression model is significant or it can be said that the influence of leadership style, organizational culture and discipline on employee performance together has a significant effect on employee performance.